DTMB-5415 Hydrodynamic Derivative Estimation Through Oblique Towing CFD Simulations - Paolo Curtolo; Simone Mancini; Ermina Begovic (Journal of Marine Science and Engineering, 2026)
Numerous studies have focused on Computational Fluid Dynamics (CFD) Unsteady Reynolds-Averaged Navier–Stokes (URANS) maneuvering simulations of benchmark ships such as the David Taylor Model Basin (DTMB) 5415 model. However, the availability of hydrodynamic derivatives obtained from verified and validated simulations at Froude numbers (Fr) of 0.41 remains limited. In this study, CFD-URANS oblique towing simulations are conducted for the DTMB 5415 benchmark hull at Fr = 0.41 and Fr = 0.28 using STAR-CCM+. Verification and validation are performed according to ITTC guidelines for Fr = 0.41 and a drift angle of 10 degrees. The validation criterion is satisfied for the longitudinal force, side force, and yawing moment, with validation uncertainties of 13.5%, 2%, and 4%, respectively. The resulting forces and moments are fitted to derive a partial set of hydrodynamic derivatives. The CFD results are compared with SIMMAN workshop (2008) Experimental Fluid Dynamics (EFD) data, showing higher prediction accuracy for linear derivatives. At Fr = 0.41, the relative errors of Y’V and N’V are approximately 3% and 4%, while at Fr = 0.28, they are approximately 2% and 5%. Nonlinear components exhibit discrepancies exceeding 15%. Hydrodynamic coefficients show different dependencies on Fr, consistent with previous studies.

Beyond the ban: Bacterial microbiota analysis of Hermetia illucens larvae meat-fed in the context of EU regulation. - Gabriele Spatola; Emma Copelotti; Simone Mancini; Asia Zanzot; Roberta Nuvoloni; Angela Trocino; Alice Giusti; Andrea Armani (Food Research International, 2026)

Numerical study on the leakage characteristic of the damaged LNG carrier in different wind scenarios - XinLong Zhang; QingYi Qu; Simone Mancini; Li Lin; YiHua Su; RenQing Zhu (Ocean Engineering, 2026)

Nonlinear motions and dynamic intermittency of planing hulls in random wave fields: A structure-function approach - Sasan Tavakoli; Rasul Niazmand Bilandi; Simone Mancini; Cagil Kirezci (Ocean Engineering, 2026)

Growth performances of gilthead seabream (Sparus aurata) fed alternative diets for “circular” land-based IMTA production - Lorenzo Rossi; Carlo Bibbiani; Francesca Conti; Chiara Sangiacomo; Ilaria Marchioni; Elisa Merega; Simone Mancini; Alberto Pardossi; Baldassare Fronte (Aquaculture, 2025)

Traditional Middle Eastern spice blends (Baharat): Antimicrobial activity, metabolomic profile, and trace element analysis - Mauro Di Stasi; Ata Kaboudari; Mancini Simone; Veronique Vacchina; Alessandra Braca; Marinella De Leo; Filippo Fratini (Phytochemistry Letters, 2025)

Analyses of Different Approaches for Virtual Towing Tank Uncertainty Assessment - Simone Bozzo; Diego Villa; Simone Mancini (Journal of Marine Science and Engineering, 2025)
The assessment for the resistance of a new ship under design can be performed through the Experimental Fluid Dynamics (EFD) or the Computational Fluid Dynamics (CFD) approach; both have their own Uncertainty Assessment (UA). In CFD field, the Verification and Validation (V&V) procedures take into account the approximations for numerical issues and the assumptions adopted to describe the physical phenomena to assess UA. Different theoretical approaches have become available over time; nevertheless, a single comprehensive solution to achieve the UA remains still unknown because as the theoretical methodology varies, the outcome changes. In current work, four different literature approaches will be augmented to perform a V&V analysis for two kinds of model hulls, tested at different speeds and compared with the experimental data. The investigations performed among results lead to the division of all the approaches into the three and four solutions families and to define a robust procedure to identify a reasonable value for the numerical uncertainty assessment. Regarding the robustness and the UA of the approaches, the first family proved successful in only 55% of cases with a UA mean value below 2.01%, while the second one always provides a quantification but with a mean value of 6.65%.

VegRecoverAI: A deep learning-based system for automated vegetation recovery assessment and prediction with demonstration case study on gas pipeline construction - Alessandro Galdelli; Simone Pesaresi; Giacomo Quattrini; Roberto Pierdicca; Amal Benson Thaliath; Adriano Mancini (Environmental Modelling & Software, 2025)

A European survey on anaerobes from paediatric blood cultures: a comparative analysis with adults - Matteo Boattini; Arianna Aceti; Paulo Bastos; Viktoria Eirini Mavromanolaki; Sofia Maraki; Anastasia Spiliopoulou; Vasileios Kakouris; Yordan Kalchev; Ana Budimir; Branka Bedenić; Zana Rubic; Monica Licker; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Modeling of Marine Assembly Logistics for an Offshore Floating Photovoltaic Plant Subject to Weather Dependencies - Lu-Jan Huang; Simone Mancini; Minne de Jong (Journal of Marine Science and Engineering, 2025)
Floating solar technology has gained significant attention as part of the global expansion of renewable energy due to its potential for installation in underutilized water bodies. Several countries, including the Netherlands, have initiated efforts to extend this technology from inland freshwater applications to open offshore environments, particularly within offshore wind farm areas. This development is motivated by the synergistic benefits of increasing site energy density and leveraging the existing offshore grid infrastructure. The deployment of offshore floating photovoltaic (OFPV) systems involves assembling multiple modular units in a marine environment, introducing operational risks that may give rise to safety concerns. To mitigate these risks, weather windows must be considered prior to the task execution to ensure continuity between weather-sensitive activities, which can also lead to additional time delays and increased costs. Consequently, optimizing marine logistics becomes crucial to achieving the cost reductions necessary for making OFPV technology economically viable. This study employs a simulation-based approach to estimate the installation duration of a 5 MWp OFPV plant at a Dutch offshore wind farm site, started in different months and under three distinct risk management scenarios. Based on 20 years of hindcast wave data, the results reveal the impacts of campaign start months and risk management policies on installation duration. Across all the scenarios, the installation duration during the autumn and winter period is 160% longer than the one in the spring and summer period. The average installation durations, based on results from 12 campaign start months, are 70, 80, and 130 days for the three risk management policies analyzed. The result variation highlights the additional time required to mitigate operational risks arising from potential discontinuity between highly interdependent tasks (e.g., offshore platform assembly and mooring). Additionally, it is found that the weather-induced delays are mainly associated with the campaigns of pre-laying anchors and platform and mooring line installation compared with the other campaigns. In conclusion, this study presents a logistics modeling methodology for OFPV systems, demonstrated through a representative case study based on a state-of-the-art truss-type design. The primary contribution lies in providing a framework to quantify the performance of OFPV installation strategies at an early design stage. The findings of this case study further highlight that marine installation logistics are highly sensitive to local marine conditions and the chosen installation strategy, and should be integrated early in the OFPV design process to help reduce the levelized cost of electricity.

Effect on food-related pathogens and chemical fingerprint of regional recipes of Baharat, a traditional Middle Eastern spice blend - Mauro Di Stasi; Ata Kaboudari; Simone Mancini; Veronique Vacchina; Marinella De Leo; Alessandra Braca; Filippo Fratini (Food Bioscience, 2025)

Verification and validation of hard-chine hull performance in calm water: Effects of numerical setups and hull configurations - Mikloš Lakatoš; Simone Mancini; Rasul Niazmand Bilandi; Kristjan Tabri (Ocean Engineering, 2025)

Numerical study on the dynamic RPT behavior of the damaged LPG carrier with combined CFD and VOF boiling model - XinLong Zhang; Li Lin; YiHua Su; Shan Ma; Gang Wang; Simone Mancini (Ocean Engineering, 2025)

Experimental and numerical investigation of air lubrication on a planing hull with Double Interceptor System - Vincenzo Sorrentino; Riccardo Pigazzini; Fabio De Luca; Simone Mancini; Claudio Pensa (Ocean Engineering, 2025)

Hydrodynamic Performance of High-Speed Craft: A CFD Study on Spray Rails - Muhammad Sulman; Simone Mancini; Rasul Niazmand Bilandi; Luigi Vitiello (Journal of Marine Science and Engineering, 2025)
In high-speed crafts, whisker spray increases viscous resistance by enlarging the wetted surface near the stagnation line. Spray rails (SRs) mitigate this issue by redirecting water flow, reducing the wetted surface, and lowering overall resistance. This study investigates the effect of SRs on the hydrodynamic performance of the C1 hull of Naples Systematic Series (NSS), focusing on the systematic variations in size, number, and placement. Numerical simulations, validated with towing tank results, were conducted using STAR CCM+ 2306. Mesh independence analysis was also performed to optimize computational efficiency. Key findings highlight the critical role of SR design in performance optimization. Wider SRs (e.g., three per side, 0.96% LWL) reduced resistance by up to 8.5% at high speeds (Fr∇= 3.26), but slightly increased the resistance at lower speeds (~2%) due to a larger wetted surface. Narrower SRs (e.g., three per side, 0.48% LWL) achieved resistance reductions of up to 4.6%, while configurations with multiple SRs (e.g., three per side, 0.72% LWL) outperformed single-rail designs by reducing resistance up to 4%. Placement near the chine proved more effective than near the keel, offering a 4% additional reduction in resistance. Additionally, SRs generated lift, raising the hull, and reducing immersion. The study underscores the importance of optimizing SR size, number, and placement to enhance hydrodynamic efficiency, particularly for high-speed operations.

TNBS colitis induces architectural changes and alpha-synuclein overexpression in mouse distal colon: A morphological study - Arianna Casini; Giorgio Vivacqua; Ludovica Ceci; Stefano Leone; Rosa Vaccaro; Marco Tagliafierro; Filippo Maria Bassi; Sara Vitale; Emanuele Bocci; Luigi Pannarale; Simone Carotti; Antonio Franchitto; et al. (Cell and Tissue Research, 2025)

Heavy metals (Pb, Cd, Ni) in insect-based products for human consumption sold by e-commerce in the EU market: Occurrence and potential health risk associated with dietary exposure - Andrea Gori; Andrea Armani; Francesca Pedonese; Omar Benini; Simone Mancini; Roberta Nuvoloni (Food Control, 2025)

Verification and Validation Analysis on Marine Applications - Simone Mancini; Momchil Terziev (Journal of Marine Science and Engineering, 2024)
Both users and developers of computational simulations are facing a crucial dilemma—how can confidence in modelling and simulation be properly evaluated [...]

Assessment of the information to consumers on insects-based products (Novel Food) sold by e-commerce in the light of the EU legislation: when labelling compliance becomes a matter of accuracy. - Gabriele Spatola; Alice Giusti; Simone Mancini; Lara Tinacci; Roberta Nuvoloni; Filippo Fratini; Francesco Di Iacovo; Andrea Armani (Food Control, 2024)

Experimental and Numerical Investigation into the Effects of Air–Fluid Interaction on the Dynamic Responses of a Damaged Ship - Xinlong Zhang; Simone Mancini; Fei Liu; Renqing Zhu (Journal of Marine Science and Engineering, 2024)
To accurately assess the dynamic stability of the damaged ship, this paper performs an experimental campaign and presents a feasible numerical method to analyze the effects of microscopic air–fluid interactions on the motion responses of the damaged ship. The numerical approach can be applied to solve the coupled hydrodynamic behavior between the flooding process and the motion responses of the damaged ship. The volume of fluid (VOF) method was applied to capture the interface of the free surface, while the dynamic fluid–body Interaction (DFBI) morphing technique was applied to deal with mesh adaption. In particular, the UDF (user-defined field) function was activated to realize the initial distribution of the free surface. Firstly, by comparing the experimental and numerical results, the reliability of visualizing the flooding process and dealing with the motion responses of the damaged ship was efficiently verified. The numerical flooding process was able to reproduce the hydrodynamic phenomenon well, including the flooding jet, interaction, and flow between adjacent compartments. The numerical roll motion curve of the damaged ship was consistent with that predicted in the model test, with an error in roll amplitude of no more than 4%. Secondly, based on the verified numerical method, it was seen from the results with different ventilation positions that not only the air compressibility due to varying levels of ventilation cannot be neglected in damage assessment, but also the position of the ventilation hole was crucial. This was because different positions will create different paths for the compressed air to overflow and affect air–fluid interactions. Thus, the flooding force and air-impacting force acting on the internal hull will be different. In conclusion, this paper introduces a new consideration in the damage assessment of ships.

Novel foods, old issues: Metabarcoding revealed mislabeling in insect-based products sold by e-commerce on the EU market - Alice Giusti; Gabriele Spatola; Simone Mancini; Roberta Nuvoloni; Andrea Armani (Food Research International, 2024)

Human Campylobacter spp. infections in Italy - Verena Zerbato; Stefano Di Bella; Riccardo Pol; Roberto Luzzati; Gianfranco Sanson; Simone Ambretti; Stefano Andreoni; Richard Aschbacher; Mariano Bernardo; Alessandra Bielli; Gioconda Brigante; Marina Busetti; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Numerical Investigation of Single and Double Steps in Planing Hulls - Muhammad Sulman; Simone Mancini; Rasul Niazmand Bilandi (Journal of Marine Science and Engineering, 2024)
Incorporating steps into a hull reduces the wetted surface, promoting improved hydrodynamic lift and reduced resistance at high speeds, provided that the step is designed appropriately. Traditional hydrodynamics studies rely on scaled model testing in towing tanks, but numerical tools offer a more efficient alternative. This study focused on investigating the hydrodynamic performance of stepped hulls by modifying the parent hull of the Naples Systematic Series (C1). The Computational Fluid Dynamics (CFD) code SIEMENS PLM STAR CCM+ version 2302 was used for simulations, including four different beam Froude numbers (FrB = 1.13, 2.22, 2.56, and 2.96) and a total of 15 hull configurations with single and double steps. By employing a three-dimensional computational analysis of multiphase flow using Dynamic Fluid–Body Interaction (DFBI) and overset mesh, various performance parameters such as resistance coefficient, dimensionless wetted surface, sinkage, and dynamic trim were analyzed. The accuracy of the CFD results was confirmed through comparison with experimental data and grid uncertainty assessment. The study demonstrated that placing a single step near the transom decreased trim and increased resistance and wetted surface. Conversely, positioning a step in the forward section reduced the trim angle at lower step heights but increased trim at higher step heights in single-stepped hulls. The application of these findings contributes to the design optimization of stepped hulls for enhanced performance in high-speed maritime applications.

A revisited verification and validation analysis for URANS simulation of planing hulls in calm water - Rasul Niazmand Bilandi; Simone Mancini; Abbas Dashtimanesh; Sasan Tavakoli (Ocean Engineering, 2024)

Experimental and numerical investigation on effects of air compressibility on dynamic performance of the damaged ship - XinLong Zhang; Mancini Simone; Fei Liu (Ocean Engineering, 2023)

High promiscuity among females of the invasive pest species Drosophila suzukii - Simone Puppato; Giulia Fiorenza; Davide Carraretto; Ludvik Marcus Gomulski; Giuliano Gasperi; Carlos Caceres; Alberto Grassi; Maria Vittoria Mancini; Antonio De Cristofaro; Claudio Ioriatti; Robin Guilhot; Anna Rodolfa Malacrida (Molecular Ecology, 2023)
Drosophila suzukii (Matsumura, 1931), the spotted‐wing drosophila, is a highly invasive fruit fly that spread from Southern Asia across most regions of Asia and, in the last 15 years, has invaded Europe and the Americas. It is an economically important pest of small fruits such as berries and stone fruits. Drosophila suzukii speciated by adapting to cooler, mountainous, and forest environments. In temperate regions, it evolved seasonal polyphenism traits which enhanced its survival during stressful winter population bottlenecks. Consequently, in these temperate regions, the populations undergo seasonal reproductive dynamics. Despite its economic importance, no data are available on the behavioural reproductive strategies of this fly. The presence of polyandry, for example, has not been determined despite the important role it might play in the reproductive dynamics of populations. We explored the presence of polyandry in an established population in Trentino, a region in northern Italy. In this area, D. suzukii overcomes the winter bottleneck and undergoes a seasonal reproductive fluctuation. We observed a high remating frequency in females during the late spring demographic explosion that led to the abundant summer population. The presence of a high degree of polyandry and shared paternity associated with the post‐winter population increase raises the question of the possible evolutionary adaptive role of this reproductive behaviour in D. suzukii .

Temperature–humidity index monitoring during two summer seasons in dairy cow sheds in Mugello (Tuscany) - Alessandro Messeri; Marco Mancini; Riccardo Bozzi; Silvia Parrini; Francesco Sirtori; Marco Morabito; Alfonso Crisci; Gianni Messeri; Alberto Ortolani; Bernardo Gozzini; Simone Orlandini; Luca Fibbi; et al. (International Journal of Biometeorology, 2023)
Many studies have reported that the impact of high temperatures affects physiology, welfare, health, and productivity of farm animals, and among these, the dairy cattle farming is one of the livestock sectors that suffers the greatest effects. The temperature–humidity index (THI) represents the state of the art in the evaluation of heat stress conditions in dairy cattle but often its measurement is not carried out in sheds. For this reason, the aim of this study was the monitoring of the THI in three dairy cattle farms in Mugello (Tuscany) to understand its influence on dairy cows. THI values were calculated using meteorological data from direct observation in sheds and outdoor environments. Data relating to the animal’s behavior were collected using radio collars. The Pearson test and Mann–Kendall test were used for statistical analysis. The results highlighted a significant ( P < 0.001) upward trend in THImax during the last 30 years both in Low Mugello (+ 1.1 every 10 years) and in High Mugello (+ 0.9 every 10 years). In Low Mugello sheds, during the period 2020–2022, more than 70% of daytime hours during the summer period were characterized by heat risk conditions (THI > 72) for livestock. On average the animals showed a significant ( P < 0.001) decrease in time spent to feeding and rumination, both during the day and the night, with a significant ( P < 0.001) increase in inactivity. This study fits into the growing demand for knowledge of the micro-climatic conditions within farms in order to support resilience actions for protecting both animal welfare and farm productivity from the effects of climate change. This could also be carried out thanks to estimation models which, based on the meteorological conditions forecast, could implement the thermal stress indicator (THI) directly from the high-resolution meteorological model, allowing to get a prediction of the farm’s potential productivity loss based on the expected THI.

Comparative study of experimental and CFD results for stepped planing hulls - Rasul Niazmand Bilandi; Abbas Dashtimanesh; Simone Mancini; Luigi Vitiello (Ocean Engineering, 2023)

Correction: Capasso et al. Regular Wave Seakeeping Analysis of a Planing Hull by Smoothed Particle Hydrodynamics: A Comprehensive Validation. J. Mar. Sci. Eng. 2023, 11, 700 - Salvatore Capasso; Bonaventura Tagliafierro; Simone Mancini; Iván Martínez-Estévez; Corrado Altomare; José M. Domínguez; Giacomo Viccione (Journal of Marine Science and Engineering, 2023)
In the original publication [...]

Regular Wave Seakeeping Analysis of a Planing Hull by Smoothed Particle Hydrodynamics: A Comprehensive Validation - Salvatore Capasso; Bonaventura Tagliafierro; Simone Mancini; Iván Martínez-Estévez; Corrado Altomare; José M. Domínguez; Giacomo Viccione (Journal of Marine Science and Engineering, 2023)
In this work, the dynamics of a planing hull in regular head waves was investigated using the Smoothed Particle Hydrodynamics (SPH) meshfree method. The simulation of the interaction of such vessels with wave trains features several challenging characteristics, from the complex physical interaction, due to large dynamic responses, to the likewise heavy numerical workload. A novel numerical wave flume implemented within the SPH-based code DualSPHysics fulfills both demands, guaranteeing comparable accuracy with an established proprietary Computational Fluid Dynamics (CFD) solver without sharpening the computational load. The numerical wave flume uses ad hoc open-boundary conditions to reproduce the flow characteristics encountered by the hull during its motion, combining the current and waves while adjusting their properties with respect to the vessel’s experimental towing speed. It follows a relatively small three-dimensional domain, where the potentiality of the SPH method in modeling free-surface flows interacting with moving structures is unleashed. The results in different wave conditions show the feasibility of this novel approach, considering the overall good agreement with the experiments; hence, an interesting alternative procedure to simulate the seakeeping test in several marine conditions with bearable effort and satisfying accuracy is established.

Engaging in entomophagy: The role of food neophobia and disgust between insect and non-insect eaters - Giovanni Sogari; Francesco Riccioli; Roberta Moruzzo; Davide Menozzi; Daylan Amelia Tzompa Sosa; Jie Li; Aijun Liu; Simone Mancini (Food Quality and Preference, 2023)

Dynamic of Tunneled Planing Hulls in Waves - Fatemeh Roshan; Sasan Tavakoli; Simone Mancini; Abbas Dashtimanesh (Journal of Marine Science and Engineering, 2022)
A tunneled planing craft is a high-speed boat with two tunnels over the hull bottom that are designed to improve the vessel’s performance. Hydrodynamic performance of tunneled planing hulls in calm-water is well-known, however, current information on wave conditions is limited. In this study, two different tunneled planing hulls with two degrees of freedom in heave and pitch motions are studied in regular waves by using the computational fluid dynamics (CFD) method based on the Unsteady Reynolds Averaged Navier-Stokes Equations (URANSE) in conjunction with k−ϵ turbulence model. The results demonstrate that tunneled planing hull motions in waves are nonlinear. In addition, it is found that the dynamic responses of heave and pitch motions as well as occurrence portability of the fly-over phenomenon significantly increases as the Froude number grows. Fly-over motions resulted in vertical motions and acceleration up to 5g, high impact pressure, and large induced drag. At a very high planing speed, after flying over the water surface, when the vessel re-enters the water, the resulting hydrodynamic load leads to a second fly-over motion. Since the fly-over is an unwanted movement with adverse effects, these results can provide a better understanding of the fly-over motion that one may consider in future design for improving the planing hull performance.

Shipping Decarbonization: An Overview of the Different Stern Hydrodynamic Energy Saving Devices - Flaminia Spinelli; Simone Mancini; Luigi Vitiello; Rasul Niazmand Bilandi; Maria De Carlini (Journal of Marine Science and Engineering, 2022)
In recent years, research into ships has focused on reducing emissions, consuming less energy, and being more efficient. As a result, the maritime industry has been continuing in a green and sustainable direction. Improving the fuel efficiency of ships and the decarbonization of shipping are important issues to reduce fuel consumption and emitted Greenhouse Gas (GHG) amounts. Decarbonization in the shipping industry could be achieved through technical and operational strategies such as Energy Saving Devices (ESDs) to reduce the fuel consumption of new and existing ships. According to the makers, ESDs can optimize fuel efficiency by up to 15%. This paper reviews the current literature on stern hydrodynamic ESDs, which are mainly used on typical merchant vessels, i.e., bulkers, tankers, and carriers. A comprehensive review is carried out analysing the different available solutions for stern hydrodynamic ESDs, the working principles, the methods used for the design, optimization, and evaluation of the performance improvements, and the relevant issues of these specific ESDs.

Trophic, Chemo-Ecological and Sex-Specific Insights on the Relation Between Diplodus sargus (Linnaeus, 1758) and the Invasive Caulerpa cylindracea (Sonder, 1845) - Andrea Miccoli; Emanuele Mancini; Marco Boschi; Francesca Provenza; Veronica Lelli; Francesco Tiralongo; Monia Renzi; Antonio Terlizzi; Simone Bonamano; Marco Marcelli (Frontiers in Marine Science, 2021)
Biological invasions result in negative and unpredictable impacts on oceans worldwide. Non-indigenous macrophytes often synthesize secondary metabolites for defensive purposes and increased competition efficiency: this is the case of Caulerpa cylindracea , which has entered the Mediterranean Sea in 1990 and competed against local flora and fauna since. It was demonstrated that the white seabream Diplodus sargus (i) has included the algae into its diet, (ii) is subject to the peculiar Abnormally Tough Specimen (ATS) condition post-cooking, and (iii) suffers physiological and behavioral disturbances from caulerpin, one of the three major algal secondary metabolites. This paper confirms a feeding relationship between the fish and the algae, quantifies caulerpin accumulation in the liver, suggests a possible mollusk- and echinoderm-driven biomagnification, and highlights the fact that all ATS specimens were males. Multivariate analyses on a multi-biomarker panel reveals differential correlations to key cellular processes such as oxidative stress, metabolism, neurotoxicity, and lipid peroxidation as well as to condition indexes.

Evaluation of the in vitro antibacterial activity of some essential oils and their blends against Staphylococcus spp. isolated from episodes of sheep mastitis - Filippo Fratini; Margherita Giusti; Simone Mancini; Francesca Pisseri; Basma Najar; Luisa Pistelli (Rendiconti Lincei. Scienze Fisiche e Naturali, 2021)
Staphylococcus aureus and coagulase-negative staphylococci are among the major causes of mastitis in sheep. The main goal of this research was to determine the in vitro antibacterial activity of several essential oils (EOs, n 30), then five of them were chosen and tested alone and in blends against staphylococci isolates. Five bacteria were isolated from episodes of ovine mastitis (two S. aureus and three S. xylosus ). Biochemical and molecular methods were employed to identify the isolates and disk diffusion method was performed to determine their antimicrobial-resistance profile. The relative percentage of the main constituents in the tested essential oils and their blends was detected by GC-EIMS analysis. Antibacterial and bactericidal effectiveness of essential oils and blends were evaluated through minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC). All of them showed sensitivity to the used antimicrobials. The EOs with the highest antibacterial activity were those belonging to the Lamiaceae family characterized by high concentrations of thymol, carvacrol and its precursor p -cymene, together with cinnamon EO, rich in cinnamaldehyde. In terms of both MIC and MBC values, the blend composed by Thymus capitatus EO 40%, Cinnamomum zeylanicum EO 20%, Thymus serpyllum EO 20% and Satureja montana EO 20% was found to be the most effective against all the isolates. Some essential oils appear to represent, at least in vitro, a valid tool against ovine mastitis pathogens. Some blends showed a remarkable effectiveness than the single oils, highlighting a synergistic effect in relation to the phytocomplex.

Full-Scale CFD Analysis of Double-M Craft Seakeeping Performance in Regular Head Waves - Deniz Ozturk; Cihad Delen; Simone Mancini; Mehmet Ozan Serifoglu; Turgay Hizarci (Journal of Marine Science and Engineering, 2021)
This study presents the full-scale resistance and seakeeping performance of an awarded Double-M craft designed as a 15 m next-generation Emergency Response and Rescue Vessel (ERRV). For this purpose, the Double-M craft is designed by comprising the benchmark Delft 372 catamaran with an additional center and two side hulls. First, the resistance and seakeeping analyses of Delft 372 catamaran are simulated on the model scale to verify and compare the numerical setup for Fr = 0.7. Second, the seakeeping performance of the full-scale Double-M craft is examined at Fr = 0.7 in regular head waves (λ/L = 1 to 2.5) for added resistance and 2-DOF motion responses. The turbulent flow is simulated by the unsteady RANS method with the Realizable Two-Layer k-ε scheme. The calm water is represented by the flat VOF (Volume of Fluid) wave, while the incident long waves are represented by the fifth-order Stokes wave. The residual resistance of the Double-M craft is improved by 2.45% compared to that of the Delft 372 catamaran. In the case of maximum improvement (at λ/L = 1.50), the relative added resistance of the Double-M craft is 10.34% lower than the Delft 372 catamaran; moreover, the heave and pitch motion responses were 72.5% and 35.5% less, respectively.

Performance Assessment of a Planing Hull Using the Smoothed Particle Hydrodynamics Method - Bonaventura Tagliafierro; Simone Mancini; Pablo Ropero-Giralda; José M. Domínguez; Alejandro J. C. Crespo; Giacomo Viccione (Journal of Marine Science and Engineering, 2021)
Computational Fluid Dynamics simulations of planing hulls are generally considered less reliable than simulations of displacement hulls. This is due to the flow complexity around planing hulls, especially in the bow region, where the sprays are formed. The recent and constant increasing of computational capabilities allows simulating planing hull features, with more accurate turbulence models and advanced meshing procedures. However, mesh-based approaches based on the finite volume methods have shown to be limited in capturing all the phenomena around a planing hull. As such, the focus of this study is on evaluating the ability of the Smoothed Particle Hydrodynamics mesh-less method to numerically solve the 3-D flow around a planing hull and simulate more accurately the spray structures, which is a rather challenging task to be performed with mesh-based tools. A novel application of the DualSPHysics code for simulating a planing hull resistance test has been proposed and applied to the parent hull of the Naples warped planing hull Systematic Series. The drag and the running attitudes (heave and dynamic trim angle) are computed for a wide range of Froude’s numbers and discussed concerning experimental values.

Stability and Seakeeping of Marine Vessels - Ermina Begovic; Simone Mancini (Journal of Marine Science and Engineering, 2021)
Stability has always been the main safety issue for all marine vessels, and static stability evaluation is adequate for ship service [...]

Assessing the Effect of Contaminated and Restored Marine Sediments in Different Experimental Mesocosms Using an Integrated Approach and Mytilus galloprovincialis as a Model - Stefania Ancora; Federica Rossi; Marina Borgese; Cristina Pirrone; Ilaria Caliani; Simone Cappello; Giuseppe Mancini; Nicola Bianchi; Claudio Leonzio; Giovanni Bernardini; Rosalba Gornati (Marine Biotechnology, 2020)

Preliminary Investigation of Microlitter Pollution in Low-Energy Hydrodynamic Basins Using Sabella spallanzanii (Polychaeta: Sabellidae) Tubes - Daniele Piazzolla; Valentina Cafaro; Emanuele Mancini; Sergio Scanu; Simone Bonamano; Marco Marcelli (Bulletin of Environmental Contamination and Toxicology, 2020)

Wake behind a Compound Wing in Ground Effect - Saeed Jamei; Adi Maimun; Rasul Niazmand Bilandi; Nor Azwadi; Simone Mancini; Luigi Vitiello; Maria De Carlini (Journal of Marine Science and Engineering, 2020)
Flow structure is a crucial point for the conceptual design of Wing-in-Ground effect (WIG) crafts. In this study, pressure distributions around a compound wing, velocity and the turbulent intensity distribution in the wake area after trailing of the wing, have been investigated numerically. Computational simulations were completed regarding various angles of attack in-ground-effect. Two parts made up the compound wing: The first composed by one rectangular wing in the center, the second composed by a reverse taper wing, consisting of an anhedral angle at the side. A realizable k-ε turbulent model exhibited the flow field in the physical domain about the wing surface. The numerical results of the compound wing were validated using the data provided by wind tunnel tests. The flow structures around the compound wing were compared with that of a rectangular wing for different conditions. It was found that the pressure distribution on the rectangular wing was weaker than at the lower surface for the compound wing. However, the suction effect on the upper surface of the rectangular wing was higher. Also, the velocity defect and the turbulence level in the wake area was greater behind the compound wing.

Nutritional Quality, Physical Properties and Lipid Stability of Ready-to-cook Fish Products are Preserved during Frozen Storage and Oven-cooking - Yara Husein; Giulia Secci; Simone Mancini; Bruno Zanoni; Giuliana Parisi (Journal of Aquatic Food Product Technology, 2020)

Normalized Difference Vegetation Index versus Dark Green Colour Index to estimate nitrogen status on bermudagrass hybrid and tall fescue - Lisa Caturegli; Monica Gaetani; Marco Volterrani; Simone Magni; Alberto Minelli; Ada Baldi; Giada Brandani; Marco Mancini; Anna Lenzi; Simone Orlandini; Filippo Lulli; Claudia de Bertoldi; et al. (International Journal of Remote Sensing, 2020)

Molecular phylogeny and host‐plant use (Lamiaceae) of the Thymogethes pollen beetles (Coleoptera) - Simone Sabatelli; Meike Liu; Davide Badano; Emiliano Mancini; Marco Trizzino; Andrew Richard Cline; Anders Endrestøl; Min Huang; Paolo Audisio (Zoologica Scripta, 2020)
The 24 members of the Euro‐Asiatic genus Thymogethes are highly specialized pollen beetles associated as larvae with flowers of Lamiaceae Nepetoideae. All members of the genus were analysed in within the framework of an integrative taxonomy approach, which was aimed to reconstruct the phylogenetic relationships, as well as the possible pattern of evolution of their larval‐host‐plant association. Evidence from multiple molecular markers [COI; 16S; H3], combined with an estimation of divergence times using an average rate of 0.0177 substitutions/site/My among branches, placed the origin of the genus at a minimum of 9–10 Mya. This date of origin approximates the known evolution of the host plants in Euro‐Mediterranean areas. Evidence from combined molecular and cladistic morphological analyses resulted in suitable agreement with the previously established morphology‐based systematics of the genus, although members of the exilis species‐group were split into three clades. The only disagreement between results of this new combined phylogeny and previous classification is in the exclusion of “ Thymogethes ” grenieri . This species is herein positioned outside the genus, based on molecular evidence. Our analysis depicts several Thymogethes species differentiating in the last few Mys, specifically those included in the T. lugubris species‐group. Combined evidence from DNA, morphology and ancestral state parsimony reconstruction of larval‐host‐plant associations suggests that subtribe Menthinae likely represents the ancestral host plants, with a series of independent host shifts during the radiation of the clade, in association first with Menthinae and subsequently with Lavandulinae and Nepetinae. Steno‐oligophagy is the most frequent (86%) condition, while strictly monophagous species are less numerous (14%).

Numerical Investigation into the Effect of Damage Openings on Ship Hydrodynamics by the Overset Mesh Technique - Xinlong Zhang; Zhuang Lin; Simone Mancini; Ping Li; Dengke Liu; Fei Liu; Zhanwei Pang (Journal of Marine Science and Engineering, 2019)
Damage stability is difficult to assess due to the complex hydrodynamic phenomena regarding interactions between fluid and structures. Therefore, a detailed analysis of the flooding progression and motion responses is important for improving ship safety. In this paper, numerical simulations are performed on the damaged DTMB 5415 ship at zero speed. All calculation are carried out using CD Adapco Star CCM + software, investigating the effect of damage openings on ship hydrodynamics, including the side damage and the bottom damage. The computational domain is modelled by the overset mesh and solved using the unsteady Reynold-average Navier-Stokes (URANS) solver. An implicit solver is used to find the field of all hydrodynamics unknown quantities, in conjunction with an iterative solver to solve each time step. The Volume of Fluid (VOF) method is applied to visualize the flooding process and capture the complex hydrodynamics behaviors. The simulation results indicated that two damage locations produce the characteristic flooding processes, and the motion responses corresponding to the hydrodynamic behaviors are different. Through comparative analysis, due to the difference between the horizontal impact on the longitudinal bulkhead and the vertical impact on the bottom plate, the bottom damage scenario always has a larger heel angle than the side damage scenario in the same period. However, the pitch motions are basically consistent. Generally, the visualization of the flooding process is efficient to explain the causes of the motion responses. Also, when the damage occurs, regardless of the bottom damage or the side damage, the excessive heel angle due to asymmetric flooding is often a threat to ship survivability with respect to the pitch angle.

Mesocosm System to Evaluate BF-MBR Efficacy in Mitigating Oily Wastewater Discharges: an Integrated Study on Mytilus galloprovincialis - Rosalba Gornati; Maria Maisano; Cristina Pirrone; Tiziana Cappello; Federica Rossi; Marina Borgese; Alessia Giannetto; Simone Cappello; Giuseppe Mancini; Giovanni Bernardini; Salvatore Fasulo (Marine Biotechnology, 2019)

Comparative serum bactericidal activity of meropenem-based combination regimens against extended-spectrum beta-lactamase and KPC-producing Klebsiella pneumoniae - Paolo Gaibani; Donatella Lombardo; Michele Bartoletti; Simone Ambretti; Caterina Campoli; Maddalena Giannella; Sara Tedeschi; Matteo Conti; Rita Mancini; Maria Paola Landini; Maria Carla Re; Pierluigi Viale; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

A Numerical Investigation on the Flooding Process of Multiple Compartments Based on the Volume of Fluid Method - XinLong Zhang; Zhuang Lin; Simone Mancini; Ping Li; Ze Li; Fei Liu (Journal of Marine Science and Engineering, 2019)
A detailed description of the flooding process is crucial to analyze the complex hydrodynamic behaviors and enhance the survivability of the damaged ship. In this paper, through establishing three typical damage scenarios with various locations, the commercial software CD Adapco STAR-CCM+ based on the Reynolds-Averaged Navier-Stokes (RANS) solver is applied to simulate the flooding process involving multiple compartments. The basic computational fluid dynamics (CFD) models and specific simulation settings are elaborated. The volume of fluid (VOF) method combined with the user defined field function is developed to distribute the initial free surface. The captured flooding process indicates that the air compression due to the restricted ventilation decreases the flooding amount. The obtained flooding time can provide necessary data to support for appropriate rescue management and evacuation options.

Sub-inhibitory concentration of essential oils induces antibiotic resistance in Staphylococcus aureus - Barbara Turchi; Simone Mancini; Luisa Pistelli; Basma Najar; Filippo Fratini (Natural Product Research, 2019)

A Validation of Symmetric 2D + T Model Based on Single-Stepped Planing Hull Towing Tank Tests - Rasul Niazmand Bilandi; Simone Mancini; Luigi Vitiello; Salvatore Miranda; Maria De Carlini (Journal of Marine Science and Engineering, 2018)
In the current article, the hydrodynamic forces of single-stepped planing hulls were evaluated by an analytical method and compared against towing tank tests. Using the 2D + T theory, the pressure distribution over the wedge section entering the water and the normal forces acting on the 2D sections have been computed. By integrating the 2D sectional normal forces over the entire wetted length of the vessel, the lift force acting on it has been obtained. Using lift forces as well as the consequence pitch moment, the equilibrium condition for the single-stepped planing hull is found and then resistance, dynamic trim, and the wetted surface are computed. The obtained hydrodynamic results have been compared against the experimental data and it has been observed that the presented mathematical model has reasonable accuracy, in particular, up to Froude number 2.0. Furthermore, this mathematical model can be a useful and fast tool for the stepped hull designers in the early design stage in order to compare the different hull configurations. It should also be noted that the mathematical model has been developed in such a way that it has the potential to model the sweep-back step and transverse the vertical motions of single-stepped planing hulls in future studies.

Sub-inhibitory stress with essential oil affects enterotoxins production and essential oil susceptibility in Staphylococcus aureus - Barbara Turchi; Simone Mancini; Luisa Pistelli; Basma Najar; Domenico Cerri; Filippo Fratini (Natural Product Research, 2018)

Shell fluctuating asymmetry in the sea-dwelling benthic bivalve Mytilus galloprovincialis (Lamarck, 1819) as morphological markers to detect environmental chemical contamination - Massimiliano Scalici; Lorenzo Traversetti; Federica Spani; Valentina Malafoglia; Monica Colamartino; Tiziana Persichini; Simone Cappello; Giuseppe Mancini; Giulia Guerriero; Marco Colasanti (Ecotoxicology, 2017)

Morphological, genetic and host-plant diversification in pollen-beetles of the Brassicogethes coracinus group (Coleoptera: Nitidulidae: Meligethinae) - Emiliano Mancini; Alessio De Biase; Andrew Richard Cline; Gloria Antonini; Marco Trizzino; Tom Clayhills; Simone Sabatelli; Pierfilippo Cerretti; Paolo Audisio (Rendiconti Lincei. Scienze Fisiche e Naturali, 2016)

The “SYSTEMS BIOLOGY” in the study of xenobiotic effects on marine organisms for evaluation of the environmental health status: biotechnological applications for potential recovery strategies - Salvatore Fasulo; Giulia Guerriero; Simone Cappello; Marco Colasanti; Trifone Schettino; Claudio Leonzio; Giuseppe Mancini; Rosalba Gornati (Reviews in Environmental Science and Bio/Technology, 2015)

STRANgE, integrated physical–biological–mechanical system for recovery in of the “oil spill” in Antarctic environment - Simone Cappello; Giuseppe Mancini; Alessandro Pistone; Maurizio Azzaro; Francesco Bottino; Lucrezia Genovese; Daniela Iannazzo; Antonella Luciano; Antonino Mamo; Giovanni Neri; Signorino Galvagno; Santina Santisi; et al. (Reviews in Environmental Science and Bio/Technology, 2014)

Preliminary evaluation of probiotic potential of Lactobacillus plantarum strains isolated from Italian food products - Barbara Turchi; Simone Mancini; Filippo Fratini; Francesca Pedonese; Roberta Nuvoloni; Fabrizio Bertelloni; Valentina Virginia Ebani; Domenico Cerri (World Journal of Microbiology and Biotechnology, 2013)

Mediterranean climate patterns and wine quality in North and Central Italy - John David Dalu; Marina Baldi; Anna Dalla Marta; Simone Orlandini; Gianpiero Maracchi; Giovanni Dalu; Daniele Grifoni; Marco Mancini (International Journal of Biometeorology, 2013)

Benthic diatom assemblages and their response to human stress in small-sized volcanic-siliceous streams of central Italy (Mediterranean eco-region) - Valentina Della Bella; Giorgio Pace; Mariachiara Barile; Andrea Zedde; Camilla Puccinelli; Simone Ciadamidaro; Pier Paolo Danieli; Paolo Andreani; Francesca Anna Aulicino; Carlo Belfiore; Laura Mancini (Hydrobiologia, 2012)